Interneuron Progenitor Transplantation to Treat CNS Dysfunction - Chohan, Muhammad O.; Moore, Holly (Frontiers in Neural Circuits, 2016)
Due to the inadequacy of endogenous repair mechanisms diseases of the nervous system remain a major challenge to scientists and clinicians. Stem cell based therapy is an exciting and viable strategy that has been shown to ameliorate or even reverse symptoms of CNS dysfunction in preclinical animal models. Of particular importance has been the use of GABAergic interneuron progenitors as a therapeutic strategy. Born in the neurogenic niches of the ventral telencephalon, interneuron progenitors retain their unique capacity to disperse, integrate and induce plasticity in adult host circuitries following transplantation. Here we discuss the potential of interneuron based transplantation strategies as it relates to CNS disease therapeutics. We also discuss mechanisms underlying their therapeutic efficacy and some of the challenges that face the field.